2017
DOI: 10.1007/s00438-017-1371-8
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome profiling of fully open flowers in a frost-tolerant almond genotype in response to freezing stress

Abstract: Spring frost is a major limiting abiotic stress for the cultivation of almonds [Prunus dulcis (Mill.)] in Mediterranean areas or the Middle East. Spring frost, in particular, damages almond fully open flowers, resulting to significant reduction in yield. Little is known about the genetic factors expressed after frost stress in Prunus spp. as well as in almond fully open flowers. Here, we provide the molecular signature of pistils of fully open flowers from a frost-tolerant almond genotype. The level of frost t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Primers for the IGT family members were designed using the respective QUIAGEN CLC Genomics Workbench tool (QUIAGEN, https://digitalinsights.qiagen.com/). Actin primers were used as an internal control to normalize expression [56]. The reactions were performed using a 7900 DNA sequence detector (Thermo Fisher Scientific, https://www.thermofisher.com).…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
“…Primers for the IGT family members were designed using the respective QUIAGEN CLC Genomics Workbench tool (QUIAGEN, https://digitalinsights.qiagen.com/). Actin primers were used as an internal control to normalize expression [56]. The reactions were performed using a 7900 DNA sequence detector (Thermo Fisher Scientific, https://www.thermofisher.com).…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
“…In another study, transcriptome analysis of a frost-tolerant genotype in response to freezing stress using RNA-Seq method revealed 863 upregulated genes and 555 downregulated genes in the frost-treated library. In this study, a highly expressed cold-shock protein was identified which can be used as a marker in future studies [17].…”
Section: Transcriptome and Proteomementioning
confidence: 99%
“…decumbens in response to cold stress -cold sensor or signal transduction genes GeneID and expression patterns of DEGs in C. japonica var. decumbens in response to cold stress -genes related to the stabilization of the plasma membrane and osmosensing response acclimation-related transcriptome of C. japonica (Li et al 2016), and in cold-related transcriptome studies with other woody species such as Hevea brasiliensis (Cheng et al 2018), Eucalyptus nitens (Gaete-Loyola et al 2017), or Prunus dulcis (Hosseinpour et al 2018). Dozens of cold related genes with known function in other model plants were found in this differential expression list, including cold sensor or signal transduction genes, cold responsive transcription factor genes, plasma membrane stabilization related genes and osmosensing-responsive genes.…”
Section: Figurementioning
confidence: 99%